Excessiveness Concept in Architecture - Ali Mohsen Jaafar Al-kafaji; Zainab Ismael Abd Al-kadum AlRubaiey (Engineering and Technology Journal, 2014)
The concept of excessive emerged as one of the concepts of contemporary architecture. This quantum of information led us to neediness searching for literature and previous studies on this concept and discover the knowledge gap in it, that resulted research problem which is (the lack of a comprehensive framework describes to the concept of excessive ,aspects associated with it, and the formula and the levels achieved in contemporary architecture), so identified targets search For the definition of this concept and everything related by the goal of search have been associated with: formulation of excessiveness theoretical framework in thought, language, and science to start studying the intellectual and scientific foundations in architecture in general. particularly the goal concentrates in effort to reached the what the excessive output is. and make the excessiveness theoretical framework and its generated technology. as for the taken approach in this search first it has been study the intellectual aspects then it has been follow-up his appearance in the architectural outputs. after that it goes to theoretical framework and determination the vocabulary from it. then it has been select the measures of application and finally puts the results and its conclusions.